(untitled) (Journal of Engineering, 2015)
In recent years, the performance of Spatial Data Infrastructures for governments and companies is a task that has gained ample attention. Different categories of geospatial data such as digital maps, coordinates, web maps, aerial and satellite images, etc., are required to realize the geospatial data components of Spatial Data Infrastructures. In general, there are two distinct types of geospatial data sources exist over the Internet: formal and informal data sources. Despite the growth of informal geospatial data sources, the integration between different free sources is not being achieved effectively. The adoption of this task can be considered the main advantage of this research. This article addresses the research question of how the integration of free geospatial data can be beneficial within domains such as Spatial Data Infrastructures. This was carried out by suggesting a common methodology that uses road networks information such as lengths, centeroids, start and end points, number of nodes and directions to integrate free and open source geospatial datasets. The methodology has been proposed for a particular case study: the use of geospatial data from OpenStreetMap and Google Earth datasets as examples of free data sources. The results revealed possible matching between the roads of OpenStreetMap and Google Earth datasets to serve the development of Spatial Data Infrastructures.